APEX2‐mediated RAB proximity labeling identifies a role for RAB21 in clathrin‐independent cargo sorting. (4th January 2019) - Del Olmo, Tomas; Lauzier, Annie; Normandin, Caroline; Larcher, Raphaëlle; Lecours, Mia; Jean, Dominique; Lessard, Louis; Steinberg, Florian; Boisvert, François‐Michel; Jean, Steve
Abstract: RAB GTPases are central modulators of membrane trafficking. They are under the dynamic regulation of activating guanine exchange factors (GEFs) and inactivating GTPase‐activating proteins (GAPs). Once activated, RABs recruit a large spectrum of effectors to control trafficking functions of eukaryotic cells. Multiple proteomic studies, using pull‐down or yeast two‐hybrid approaches, have identified a number of RAB interactors. However, due to the in vitro nature of these approaches and inherent limitations of each technique, a comprehensive definition of RAB interactors is still lacking. By comparing quantitative affinity purifications of GFP:RAB21 with APEX2‐mediated proximity labeling of RAB4a, RAB5a, RAB7a, and RAB21, we find that APEX2 proximity labeling allows for the comprehensive identification of RAB regulators and interactors. Importantly, through biochemical and genetic approaches, we establish a novel link between RAB21 and the WASH and retromer complexes, with functional consequences on cargo sorting. Hence, APEX2‐mediated proximity labeling of RAB neighboring proteins represents a new and efficient tool to define RAB functions. Synopsis: Quantitative affinity purification combined with mass spectrometry (AP‐MS) and APEX2‐mediated proximity labeling of early endosomal RAB GTPases identify a novel interaction between RAB21 and the WASH/retromer complexes. Functional validation of the proteomic data defines a role for RAB21 in endosomal sorting of a subset of clathrin‐independent cargos. Unbiased proteomics establish a network of early endosomal RAB interacting and neighboring proteins. RAB21 interacts with the WASH and retromer complexes, and acts as a modulator of F‐actin generation at endosomes. RAB21 regulates sorting of a subset of clathrin‐independent cargos, such as MCT1, SLC3A2, Basigin and CD44. Abstract : Quantitative proteomics and APEX2‐mediated proximity labeling of early endosomal RAB GTPases identify a novel interaction between RAB21 and the WASH/retromer complexes and defines a role for RAB21 in endosomal sorting of a subset of clathrin‐independent cargos.